2020
DOI: 10.1111/jfr3.12627
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the danger to life in flash flood events adopting a mechanics based methodology and planning evacuation routes

Abstract: Extreme flood events are becoming more frequent and challenging due to climate change. Key objectives of this study are to evaluate different criteria used in assessing the hazard to people during flood events and, once determined, the most suitable method is then used to assess the hazard and the safest route(s) for evacuation during a flood event and for a particular case study. The results of the application of two criteria are analysed in terms of the flood hazard assessment with the two criteria being bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Topographic data for modelling have been extrapolated from LIDAR (Laser Imaging Detection and Ranging) data collected during a survey undertaken by the Environment Agency after the flood event. Constant roughness (Manning's coefficient) equal to 0.040 has been used for the whole catchment (Kvočka et al 2015;Musolino et al 2020b). The frequency of the flood event was estimated to be 1:400 years, with the peak discharge of the event estimated to be about 180 m 3 /s (HR Wallingford 2005;Roca and Davison 2010).…”
Section: Boscastlementioning
confidence: 99%
“…Topographic data for modelling have been extrapolated from LIDAR (Laser Imaging Detection and Ranging) data collected during a survey undertaken by the Environment Agency after the flood event. Constant roughness (Manning's coefficient) equal to 0.040 has been used for the whole catchment (Kvočka et al 2015;Musolino et al 2020b). The frequency of the flood event was estimated to be 1:400 years, with the peak discharge of the event estimated to be about 180 m 3 /s (HR Wallingford 2005;Roca and Davison 2010).…”
Section: Boscastlementioning
confidence: 99%
“…Elevation data from remote sensing (Neal et al., 2009; Yu & Lane, 2006) can be very detailed but they show limitations as they can be obscured by surrounding buildings and other obstacles. Moreover, flood hazard mapping requires not only the inundation extent and the flow depth but also the flow velocities (Costabile et al., 2020; Musolino et al., 2020; Xia et al., 2014), which are very hard and potentially dangerous to obtain in flood conditions. As a result, only a few studies have reported flow velocity data from measurements in urban floods.…”
Section: Introductionmentioning
confidence: 99%
“…if catchments have undergone significant land use change, experience more extreme rainfalls than previously recorded or see significantly changed streamflow characteristics due to the building of human infrastructure (Jain and Lall, 2001). Long-term planning in non-stationary systems requires a move away from traditional empirical approaches (widely used in operational engineering hydrology) towards process-based models which are necessarily more complex and require deeper process understanding (Milly et al, 2008;Wagener et al, 2010;Clark et al, 2015;Musolini et al, 2020). Process-based models -increasingly with unprecedented resolutions -will also demand better computational skills of their users to utilise them effectively and thus influence training and education (Hut et al, 2017).…”
Section: Introductionmentioning
confidence: 99%